AESTHETIC TRANSFORMATION OF PEKALONGAN BATIK: INTEGRATING TRADITIONAL ART INTO THE CREATIVE ECONOMY - Samudra, Dio; Ismanto, Kuat (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2025)
Pekalongan batik, recognized as UNESCO Intangible Cultural Heritage since 2009, faces contemporary challenges in maintaining relevance within the global creative economy while preserving its cultural authenticity. The integration of aesthetic dimensions into traditional craft development has become critical for sustainable transformation. A qualitative approach was employed through literature review and descriptive analysis, examining academic publications, government reports, and industrial documentation of Pekalongan batik industry.The application of aesthetic dimensions—encompassing visual, tactile, and symbolic aspects—significantly enhanced product competitiveness. The Triple Helix Contribution among universities, industry, and government yielded a 35% increase in product innovation. Modern geometric motifs demonstrated 40% higher demand in export markets, while online sales grew 65% over two years. Export value reached USD 45 million in 2023, representing a 30% annual increase, with an average 150% value addition through design innovation.Systematic integration of traditional aesthetic values with contemporary market demands through collaborative innovation frameworks effectively enhances global competitiveness while maintaining cultural authenticity. This research provides strategic insights for traditional craft industries in developing sustainable transformation models within the creative economy paradigm, emphasizing the importance of multi-stakeholder Contribution and aesthetic dimension optimization.